A pragmatic outreach pilot to understand and overcome barriers to COVID‐19 vaccination in abdominal organ transplant. Issue 5 (22nd September 2021) - Serper, Marina; Liu, Chung‐Heng; Blumberg, Emily A.; Burdzy, Alexander E.; Veasey, Stephanie; Halpern, Samantha; Lander, Elaine; Sigafus, Matthew R.; Bloom, Roy D.; Dunn, Ty B.; Abt, Peter L.; Reddy, K. Rajender; et al.
Abstract: Background: Solid organ transplant recipients (SOTRs) are at increased risk for adverse outcomes with coronavirus disease 19 (COVID‐19). Early data show a lower severe acute respiratory syndrome virus 2 (SARS‐CoV‐2) spike antibody immune response among SOTRs leading to patient concerns about vaccine efficacy. Public health messaging has largely left out immunocompromized individuals leading to a higher risk of vaccine misinformation. The American Society of Transplantation recommends COVID‐19 vaccination for all SOTRs; however, patient concerns and beliefs about vaccination are largely unknown. Methods: We conducted a transplant‐center‐based, pragmatic pilot trial to encourage COVID‐19 vaccination among 103 unvaccinated SOTRs. We assessed vaccine concerns, barriers to vaccination, answered questions about efficacy, side effects, and clinical recommendations. Results: A total of 24% ( n = 25) of SOTRs reported that they will schedule COVID‐19 vaccination after the study call, 46% reported that they will consider vaccination in the future, and 30% said they will not consider vaccination. Older age and White race were associated with lower willingness to schedule the vaccine, whereas Black race and longer time from transplant were associated with higher willingness. Common vaccine concerns included lack of long‐term data, inconsistent messaging from providers, scheduling inconvenience, and insufficient resources. Follow‐up approximately 1 month after the initial outreach found 52% ( n = 13) of liver transplant recipients, and 10% ( n = 3) of kidney transplant recipients subsequently received COVID‐19 vaccines for a vaccination rate of 29% among respondents. Conclusion: Transplant center‐based vaccine outreach efforts can decrease misinformation and increase vaccination uptake; however, vaccine‐related mistrust remains high.